A random walk down Wall Street the time-tested strategy for successful investing - Malkiel, Burton G. 1932- (W.W. Norton & Company, 2020)
Whether you're considering your first 401k contribution, contemplating retirement, or anywhere in between, A Random Walk Down Wall Street is the best investment guide money can buy. In this new edition, Burt G. Malkiel shares authoratative insights spanning the full range of investment opportunities -- including valuable new material on crypocurrencies like bitcoin and "tax-loss harvesting" to help you chart a clam course through the turbulent waters of today's financial markets. --Back cover
Includes index
This 2020 paperback edition includes: "Supplement: How pork bellies acquired an ivy league suit: A primer on derivatives" and "Appendix to supplement: What determines prices in the futures and options markets?" (pages 405-446) that is not included in the 2019 hardcover edition
Keywords: Kapitalanlage; Privater Anleger; Wertpapieranlage; Investments; Stocks; Random walks (Mathematics); Nonfiction; Handbooks and manuals